Bianchi type V perfect-fluid space-times - Ram S. (My University, 2025)
A method is presented to generate exact solutions of the Einstein field equations in Bianchi type V space-times. The energy-momentum tensor is of perfect fluid type. Starting from particular solutions, new classes of solutions are obtained. The geometrical and physical properties of a class of solutions are discussed. © 1990 Plenum Publishing Corporation.